Distribution of Clinical Staphylococccus aureus Isolates and Antibiotic Resistance Profile: Three-Year Data - Muradiye Yarar; Onur Irmak; Nermin Özen; Tuğba Kula Atik; Alev Çetin Duran; Ali Korhan Sığ (Journal of Contemporary Medicine, 2022)
Objective: Staphylococci cause community-acquired and hospital-acquired infections, and Staphylococcus aureus is one of leading agents. In the last decades methicillin-resistant S.aureus (MRSA), vancomycin-intermediate S.aureus (VISA) and vancomycin-resistant S.aureus (VRSA) became as major concerns. Resistance to other antibiotics is also another growing issue. The aim of this study was to investigate the prevalence of S.aureus species and to evaluate susceptibilities to antimicrobial agents in a state (tertiary) hospital. Methods: Clinical cultures from various samples (urinary tract, respiratory, wound, abscess, tissue, catheter and external auditory) obtained from January 2017 to December 2019 in XXX hospital were included in the study. Isolated S.aureus strains and their antibiotic susceptibilities were retrospectively evaluated. Results: A total of 765 S.aureus strains were isolated. 165 S.aureus strains were found as methicillin resistant (MRSA; 21.9%). There was not any statistically significant difference in MRSA rates among evaluated years (p=0.772). There was not any strain that was resistant to vancomycin, teicoplanin and/or linezolid. The highest rate was observed in penicillin resistance (n=646/728, 88.7%). There was not any statistically significant alteration in the resistance rates of all tested antibiotics during the three-year period. Conclusions: Despite dwindling MRSA rates in UAMDSS, CAESAR report indicates that Turkey seems to be in the beginning phase of this struggle. Local and/or national antimicrobial stewardship programs are in effect in Turkey, but further measures are required.